O RACIOCÍNIO LÓGICO MATEMÁTICO DE ALUNOS SUPERDOTADOS EM RELAÇÃO AO USO DE APLICATIVOS DE DIFERENTES COMPLEXIDADES - Deliberalli, Mariangela (2017)
This research presents the development of logical mathematical reasoning and its implications in process of logical mathematical construction during the gifted children’s Formal Operational stage enrolled in Kind 1 Multifunctional Support Room in Saint Clara State School in Candói/PR. The general objective of this research was to analyze adolescents’ logical reasoning in situations which ones they have available application software. The choice of such apps was because they emphasize mathematical elements presented by Piaget. Sample was three students from Elementary School, last years; two of them from seventh year and one from eighth year. Results were there were basic, moderated and complex levels of logical reasoning, different logics with regard to presented different complexities and a similarity in each level and between each child’s different logics to solve different problems presented by apps.